2022
DOI: 10.3389/fpsyg.2022.887255
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic-Assisted Psychotherapy—A Systematic Review of Associated Psychological Interventions

Abstract: Modern clinical research on psychedelics is generating interesting outcomes in a wide array of clinical conditions when psychedelic-assisted psychotherapy is delivered to appropriately screened participants and in controlled settings. Still, a number of patients relapse or are less responsive to such treatments. Individual and contextual factors (i.e., set and setting) seem to play a role in shaping the psychedelic experience and in determining clinical outcomes. These findings, coupled with data from literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 113 publications
0
21
0
Order By: Relevance
“…There is currently little guidance on how, why, when, or for whom SERT components should be addressed in PAT. 17 Brokering the role of spirituality is frequently left up to the treatment developers or individual clinicians, who often lack training in culturally competent spiritual care. Ad hoc therapies with psycho-spiritual components that are not based on evidence, or even on best practices in spiritually integrated care, run the risk of inadvertently imposing therapist-or treatment-related worldviews on patients.…”
Section: Toward Sert Integration In Patmentioning
confidence: 99%
“…There is currently little guidance on how, why, when, or for whom SERT components should be addressed in PAT. 17 Brokering the role of spirituality is frequently left up to the treatment developers or individual clinicians, who often lack training in culturally competent spiritual care. Ad hoc therapies with psycho-spiritual components that are not based on evidence, or even on best practices in spiritually integrated care, run the risk of inadvertently imposing therapist-or treatment-related worldviews on patients.…”
Section: Toward Sert Integration In Patmentioning
confidence: 99%
“…Users show altered sense perception in their bodies, with hallucinations and synaesthesia lasting up to 10 h [ 92 , 215 ]. Some authors have reported traumatic experiences (“bad trips”) after the administration of LSD, but the treatment was not performed under controlled conditions or assisted by medical personnel [ 23 , 212 , 213 , 214 , 215 ]. For this reason, the context in which the administration of psychedelic substances takes place is essential for achieving the desired therapeutic goals.…”
Section: Claviceps Purpureamentioning
confidence: 99%
“…However, in the last decade, psychedelic-assisted psychotherapy (PAP) has emerged as an alternative strategy, one that arose in response to the crisis of new psychiatric drugs [ 20 , 21 , 22 , 23 , 24 ]. To date, there have been promising clinical trials of PAP with LSD, psilocybin and ibogaine to combat drug, alcohol and nicotine addiction [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the establishment of recent guidelines for PPI strategy in psychedelic science 62 , the lack of patient/public collaborators acknowledged in this field is still evident. In this paper, we aimed to address this issue by incorporating PPI into our scale development process, allowing us to test clinical and theoretical tenets of psychedelic preparedness 9,16 , while also identifying gaps in our understanding of the acceptability and feasibility of the scale, among end-users who would actually be using it 60,63 . This approach aligns with the principles of Community-Based Participatory Research (CBPR), which promotes equitable partnerships between researchers and communities, emphasising the value of local knowledge and expertise 64 .…”
Section: Validitymentioning
confidence: 99%
“…This phase usually involves psychoeducation, the exploration of intentions and motivations, and the cultivation of a trusting therapeutic alliance [12][13][14][15] . These diverse and often non-standardised preparatory session components 16 are thought to be important determinants of treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%